The Impact of Brand Reputation on Industries in Saudi Arabia on Mada Carpet (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2024)
This research investigates the impact of brand reputation on the Mada Carpet industry in Saudi Arabia. The study aims to examine the relationship between brand reputation and customer trust, as well as the subsequent effects on customer outcomes. A theoretical model is proposed, wherein brand reputation serves as the independent variable, customer trust acts as the mediating variable, and customer outcomes represent the dependent variable. The research employs a quantitative and qualitative research design, utilizing survey questionnaires to collect data from a sample of customers and employees in the Mada Carpet industry. The findings of this study contribute to the understanding of the significance of brand reputation and customer trust in the carpet industry, providing insights for practitioners to enhance customer outcomes. Theoretical and practical implications, limitations, and suggestions for future research are discussed based on the results obtained.